전투기 흡입구 해머쇼크 설계압력에 대한 확률론적 접근법 - 배효길(Hyo-gil Bae); 이훈식(Hoon Sik Lee); 김윤미(Yun-mi Kim); 정인면(In Myon Jeong); 이상효(SangHyo Lee); 조대영(Dae-yeong Cho) (항공우주시스템공학회지, 2019)
Inlet hammershock is the critical loads condition for designing the inlet duct structure of a fighter. The sudden flow reduction in engine compressor causes inlet hammershock with high pressure. The traditional method was used to combine extreme conditions (maximum speed, sea level altitude, and cold day) to analyze this compression wave inlet hammershock pressure. However, after the 90s there have been papers that presented the probabilistic approach for the inlet hammershock to achieve the appropriate design pressure. This study shows how to analyze the inlet hammershock pressure by making practical use of the Republic of Korea Air Force real flight usage data under probabilistic approach and then analyze approximately 30% decreased inlet hammershock pressure compared with the traditional valve. 전투기 흡입구 덕트 구조물 설계에 중요한 하중조건으로 흡입구 해머쇼크 조건이 있다. 엔진 압축기 내부유동의 갑작스런 감소에 의하여 큰 압력의 해머쇼크가 발생하게 된다. 압축충격파인 흡입구 해머쇼크 해석을 위한 전통적인 방법은 극단적인 조건들의 조합을(최대 속도, 해수면, 저온 대기) 이용하였지만, 90년대 이후 확률론적 방법을 통해 적절한 해머쇼크 설계압력을 제시한 논문들이 발표되었다. 이를 참고로 본 연구는 한국공군의 비행운용데이터를 활용하여 흡입구 해머쇼크 압력을 확률론적으로 접근하였고, 이를 통해 전통적인 방법 대비 약 30 % 감소된, 흡입구 설계용 해머쇼크 압력을 해석하였다.